Gaming practices in everyday life. An analytical operationalization of field theory by means of practice theory - Toft-Nielsen, Claus; Krogager, Stinne Gunder Strøm (MedieKultur: Journal of media and communication research, 2015)
This article investigates digital game play (gaming) as a specific media field (Bourdieu, 1984, p. 72), in which especially gaming capital (Consalvo, 2007) functions as a theoretical lens. We aim to analyse the specific practices that constitute and are constituted in and around gaming. This multitude of practices is theoretically qualified by the second generation of practice theorists, including (Bruchler & Postill, 2010; Reckwitz, 2002; Schatzki, 2008; Warde, 2005). The empirical data are drawn from qualitative studies of gamers and gaming practices (focus groups as well as participant observations), and function as exemplary cases that illustrate our theoretical arguments. Our purpose is to analytically operationalize field theory, by means of practice theory, to enhance our understanding of digital games as new media and the specific contexts and media practices herein.